2006
DOI: 10.1063/1.2360229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aggregation on thermal conduction in colloidal nanofluids

Abstract: Using effective medium theory the authors demonstrate that the thermal conductivity of nanofluids can be significantly enhanced by the aggregation of nanoparticles into clusters. Predictions of the effective medium theory are in excellent agreement with detailed numerical calculation on model nanofluids involving fractal clusters and show the importance of cluster morphology on thermal conductivity enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(227 citation statements)
references
References 21 publications
11
214
2
Order By: Relevance
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condsupporting
confidence: 49%
See 1 more Smart Citation
“…It is observed that heat conductivity first increases linearly with the degree of agglomeration, reaches a maximum at the percolation threshold and finally decreases. The raising of conductivity with size (at nanoscale) was confirmed by many authors [46][47][48][49][50][51] in the case of epoxy resin with various fillers and by Prasher et al [31,52] in the case of nanofluids.…”
Section: Final Validation Of Dependence Of the Effective Thermal Condsupporting
confidence: 49%
“…The value for is often taken equal to 1.8 and since the thermal conductivity appears to depend only weakly on its value [18,[28][29][30][31], we will here work with this value.…”
Section: Effect Of Agglomerationmentioning
confidence: 99%
“…Experimental evidence and theoretical modelling support the idea that the most effective heat transport in composites or nanofluids is achieved with rods and platelets, whereas composites with spheres conduct less efficiently [34][35][36][37]. Furthermore, a clustering of particles of any shape can significantly increase the thermal conductivity of composites [38]. Similarly Maxwell's formula for a two-phase mixture, consisting of randomly distributed, noninteracting, homogeneous spheres in a homogeneous medium can be used:…”
Section: Two-phase Modelsmentioning
confidence: 84%
“…Therefore, the interfacial zones predominantly affect the thermal conductivity of the composite [245,246]. As a result, anything that can affect the interfacial regions (e.g., geometry of particles [247][248][249][250][251][252][253], aggregation [254][255][256], interfacial pressure [257], roughness [258][259][260], and the strength of interactions at the interfaces [261][262][263][264][265]) in the composites would influence their thermal conductivity. In this section, we will review the parameters affecting the interfacial interactions and their subsequent impact on the thermal conductivity of the composites.…”
Section: Thermal Conductivitymentioning
confidence: 99%